Delay time detection and accommodation for a networked DC motor control - Apolinário, Gisele C. [UNESP]; Garcia, José Paulo F. [UNESP]; Garcia, Lizete Maria C.F. [UNESP]; Rodrigues, Fernando B. [UNESP]; Garcia, Saulo C. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a control method that is effective to reduce the degenerative effects of delay time caused by a treacherous network. In present application a controlled DC motor is part of an inverted pendulum and provides the equilibrium of this system. The control of DC motor is accomplished at the distance through a treacherous network, which causes delay time in the control signal. A predictive technique is used so that it turns the system free of delay. A robust digital sliding mode controller is proposed to control the free-delay system. Due to the random conditions of the network operation, a delay time detection and accommodation strategy is also proposed. A computer simulation is shown to illustrate the design procedures and the effectiveness of the proposed method. © 2011 IEEE.
Keywords: Discrete time systems; Fault detection; Networked control systems; Predictive control; Sliding mode control; Control methods; Control signal; DC motor control; Delay Time; Design procedure; Digital sliding mode controllers; Discrete time system; Inverted pendulum; Network operations; Predictive techniques; Random condition; Sliding modes; Computer simulation; DC motors; Power electronics; DC power transmission